Strategies to Reduce Earnings Management: The Role of Leverage, Profitability and Company Size - Frasiska Risma Yolanda; Khairudin Khairudin; Aminah Aminah (Cita konsultindo, 2024)
This research was conducted to determine the test results on the effect of financial performance in the form of leverage, profitability and company size on earnings management with a focus on all sub-sectors of holding and investment companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2022. The financial statements of a company are the data used in this study. This research is important because earnings management has a negative impact that can lead to bankruptcy for an entity, so it needs to be considered in order to prevent and minimize the impact that occurs. The findings presented in this research are based on the results of multiple linear regression tests which state that (1) leverage significantly has a positive effect on earnings management; (2) profitability has a negative and significant effect on earnings management; and further findings state (3) company size has a negative and significant effect on earnings management. The results obtained in this research are a form of empirical confirmation of the importance of taking action to minimize earnings management practices for the sustainability of the company in the future. The novelty of this research is in the object of research, namely the holding and investment company sub-sector. Keywords: Leverage, Profitability, Company Size, Earnings Management.